Unsymmetrical sp(2)-sp(3) disilenes - Bisai, Milan Kumar; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2021)
Disilenes with differently coordinated silicon atoms are not known. Here, we have shown the high yield synthesis of a range of disilenes (2-4 and 6) upon reaction of a hypersilyl silylene PhC(NtBu)(2)SiSi(SiMe3)(3) (1) with aliphatic chlorophosphines. The most striking characteristic of these disilenes is the presence of two differently coordinated Si atoms (one is three-coordinated, the other four-coordinated). The analogous reaction with Ph2PCl did not afford the desired disilene, but, surprisingly, led to the first tetraphosphinosilane (8). DFT calculations were performed to understand the bonding in disilenes and differences in reactivity of the complexes.
Keywords: chlorophosphine; DFT; disilene; hypersilylsilylene